Intorno a Boccaccio/Boccaccio e dintorni Atti del Seminario internazionale di studi (Certaldo Alta, Casa di Giovanni Boccaccio, 25 giugno 2014) - Frosini, Giovanna; ZAMPONI, STEFANO (Studi e saggi, 2015)
The volume Intorno a Boccaccio / Boccaccio e dintorni was born thanks to the international seminar held in Certaldo on 25th June 2014, and it is the ideal continuation of the intense study activity characterising the hundredth anniversary of Boccaccio's birth, to which many young scholars attended. This volume collects contributions by young and very young people, some of them at their first publication, with the aim of giving space to current new researches. The discussed topics, which do not fail to consider Boccaccio's Latin and Greek culture, touch on aspects of Italian linguistics and lexicography, on the textual tradition of Latin and Vernacular works, on the commentaries to Boccaccio's works and on the geographical universe within which the Decameron places itself.